Efficacy and safety of silymarin containing antioxidant serum as an adjuvant treatment of mild‐to‐moderate acne vulgaris: A prospective, open‐label pilot study. (31st October 2022) - Kim, Jemin; Lee, Yun Na; Lee, Joohee; Lee, Sang Gyu; Kim, Hyun; Choi, Ye Seul; Draelos, Zoe Diana; Kim, Jihee
Abstract: Background: Silymarin is the active component of milk thistle, which has antioxidant properties by scavenging free radicals and potential comedolytic properties. Aims: This study aimed to assess the efficacy and safety of 0.5% silymarin‐loaded antioxidant serum (SAS) used to treat mild‐to‐moderate acne. Patients and Methods: A prospective, open‐label pilot study was conducted. We enrolled 22 Korean acne patients who applied the 0.5% SAS on the whole face twice daily while continuing the current anti‐acne medications. Grade of acne severity, individual lesion counts, sebum output levels, skin erythema, and melanin pigmentation were assessed. Results: After a 4‐week application, the modified Global Acne Grading Score (mGAGS), Global Evaluation Acne (GEA) scale, and the acne lesion counts were significantly decreased. Sebum secretion, skin pigmentation, and erythema were also reduced during the study period, yet only the melanin pigmentation index reached statistical significance. Subgroup analysis revealed that the patients who took the low‐dose oral isotretinoin during the study period showed more noticeable improvements in skin sebum output and melanin pigmentation. Additionally, no adverse event was associated with using the 0.5% SAS. Conclusion: The 0.5% silymarin‐containing antioxidant formulation improved acne's clinical severity and related skin biophysical parameters.